If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 3t + 10 Reorder the terms: 25 = 10 + 3t Solving 25 = 10 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 25 + -3t = 10 + 3t + -3t Combine like terms: 3t + -3t = 0 25 + -3t = 10 + 0 25 + -3t = 10 Add '-25' to each side of the equation. 25 + -25 + -3t = 10 + -25 Combine like terms: 25 + -25 = 0 0 + -3t = 10 + -25 -3t = 10 + -25 Combine like terms: 10 + -25 = -15 -3t = -15 Divide each side by '-3'. t = 5 Simplifying t = 5
| 4-4a=2a+1-5a | | -24+2=m-6 | | 6h-10=15h-80 | | 14=2+2s | | 3x-11=x+21 | | 4+4b=34.4 | | 24=6+7x-5x | | 14x(5-6)= | | 2(y+1)=y-4 | | 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 |